Dual engineering of oxygen vacancies and cation substitution: Insights into electronic density redistribution for ultrahigh peroxymonosulfate activation - Zhang, Zepeng; Ouyang, Yixin; Zhou, Jiawei; Liu, Zifan; Hu, Min; Zhang, Qifeng; Li, Xiuwen; Zhang, Lan; Hang, Xiaoshuai; Li, Zijian (Separation and purification technology, 2025)
[Display omitted] •A facile surfactant-free cyanogel-NaBH4 method is synthesized transition metal oxides.•The fabricated Fe-Co-OV exhibits exceptional intrinsic activity and PMS utilization.•EPR evidence shows ●OH and SO4●- drive pollutant degradation in Fe-Co-OV/PMS system.•DFT proves that O-vacancies and cation substitution boost PMS adsorption, activation.•Toxicity evaluation confirms the system reduces eco-toxicity & improves water quality. The urgent need for efficient catalytic oxidation of persistent organic pollutants in water has spurred significant research efforts. This study introduces a novel approach using transition metal oxides (TMOs) synthesized via a facile cyanogel-NaBH4 method. By fine-tuning the electronic configuration of active center, we developed ultrathin TMOs with unique electronic states that exhibit exceptional activation of peroxymonosulfate (PMS). Our synthesized TMOs demonstrated a remarkable 3.50–11.86 times higher peroxy-bond activation efficiency than reference metal oxides (bulk Co3O4) for sulfamethazine degradation. Among these, Fe-Co-OV, incorporating oxygen vacancies and low-valent metal substitution, exhibited the highest intrinsic activity (0.0209 g m−2 min−1) and ultra-high PMS utilization efficiency (0.3302). Instrument testing confirmed the pivotal roles of •OH and SO4•− radicals in Fe-Co-OV/PMS system. Theoretical calculations further elucidated how O-vacancies and low-valent cation substitution could redistribute the density of states of the active center, upshift the O p-band center, and create an electron-rich center. This favorable electronic structure promoted PMS adsorption and activation, overcoming the unfavorable redox couple. Live-dead cell staining experiments revealed a 52.63 % increase in cell survival rates in water samples treated with Fe-Co-OV/PMS system, indicating reduced eco-toxicity and improved water quality. Overall, this study established a clear atomic-level correlation between the electronic density of the active center, oxygen vacancies, and cation substitution, providing valuable insights for the rational design of advanced oxidation process catalysts.